CD55 in cancer: Complementing functions in a non-canonical manner. (28th December 2022) - Bharti, Rashmi; Dey, Goutam; Lin, Feng; Lathia, Justin; Reizes, Ofer
Abstract: CD55, or decay accelerating factor, is a membrane lipid microdomain-associated, GPI-anchored protein implicated in the shielding of cells from complement-mediated attack via accelerating decay of C3 and C5. Loss of CD55 is associated with a number of pathologies due to hyperactivation of the complement system. CD55 is also implicated in cancer progression thought to be driven via its role in cell shielding mechanisms. We now appreciate that CD55 can signal intracellularly to promote malignant transformation, cancer progression, cell survival, angiogenesis, and inhibition of apoptosis. Outside-in signaling via CD55 is mediated by signaling pathways including JNK, JAK/STAT, MAPK/NF-κB, and LCK. Moreover, CD55 is enriched in the cancer stem cell (CSC) niche of multiple tumors including breast, ovarian, cervical, and can be induced by chemotherapeutics and hypoxic environments. CSCs are implicated in tumor recurrence and chemoresistance. Here, we review the unexpected roles of CD55 in cancer including the roles of canonical and noncanonical pathways that CD55 orchestrates. We will highlight opportunities for therapeutic targeting CD55 and gaps in the field that require more in-depth mechanistic insights. Highlights: DAF/CD55 is a GPI anchored, lipid micro domain associated cell surface protein. Canonically, CD55 protects the cells from complement-mediated attack. Non-canonically, CD55 signaling axis promotes cancer progression, chemoresistance and cancer stem cell formation. Inhibition of CD55 may offer therapeutic benefits in cancers.